The Implementation and Effect of Fixed Time Employment Agreement and Job Satisfaction On The Performance of Contract Empoyees With Compensation As A Moderating Variable - Aisa Citrabella; Dudung Hadiwijaya; Ismail Marzuki (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to identify and analyze the extent to which compensation moderates the impact of the implementation of Fixed-Term Employment Agreements and job satisfaction on employee performance at PT. XYZ. The research method used is associative with a quantitative approach, utilizing moderation regression analysis. The sample consists of 97 employees, and data analysis includes moderation regression tests, determination coefficients, and hypothesis significance testing (t-tests). The results show that Fixed Time Employment Agreement has an insignificant effect on employee performance, while job satisfaction has a significant effect on employee performance. Furthermore, the implementation of the Fixed Time Employment Agreement, even when reinforced by compensation, does not significantly enhance employee performance at PT. XYZ. Additionally, compensation does not significantly moderate the relationship between job satisfaction and employee performance at PT. XYZ.